Fibrinous pericarditis and pericardial effusion in three neonatal foals. Issue 10 (1st September 2014) - Armstrong, SK; Raidal, SL; Hughes, KJ
<x xml:space="preserve">Abstract</x> Case series Three foals, aged between 5 and 10 days, were presented for assessment of lethargy, abdominal pain and joint effusion. Fibrinous pericarditis and pericardial effusion (PE) were recognised in each foal and considered as sequelae to systemic inflammatory response syndrome (SIRS) and suspected or confirmed septicaemia. Clinical course and outcome Diagnosis of pericarditis was made in two foals by echocardiographic examination and analysis of pericardial fluid, and during postmortem examination of the third foal. In both of the foals that underwent pericardiocentesis, PE was an exudate, no bacteria were identified on cytological analysis and bacterial culture was negative. Despite apparent response to treatment, two foals died 2 and 3 weeks, respectively, after discharge from hospital. One foal was euthanased during hospitalisation. Conclusion and clinical relevance This report highlights the need to consider the development of pericarditis and PE in foals with SIRS and signs of cardiorespiratory dysfunction, and the requirement for protracted follow‐up to monitor for clinical resolution.